INVESTIGATING STUDENTS' PROBLEMS AND SOLUTIONS IN LISTENING COMPREHENSION IN THE CLASS - Maraunuela, Mieske; Nikijuluw, Renata C. G. V (Pattimura University, 2021)
This study is aimed at investigating students' problems and solutions in listening comprehension. It used survey design by employing a mixed-method where the data obtained in quantitative and qualitative. The subjects of this study were 60 Students of the English Study Program FKIP, Unpatti, especially the class of 2015 and 2016. The technique of collecting the data was a Questionnaire and Interview. This study shows that the problems in listening comprehension were categorized into several topics, such as problems related to the listening materials, problems caused by the failure to concentrate, and problems related to the listener. Mostly, the students use taking notes. Meanwhile, the problems faced by students in listening comprehension were the listening materials, problems caused by the failure to concentrate, and problems related to the listener. The solutions used by the students to overcome the problems were; increase their Vocabulary, listening to the audio, and practice with their friends. It was great for students to identify their problems and solutions in listening comprehension to improve their listening comprehension.